Pilot Scheme of Health Policy in Stroke Adjuvant Acupuncture Therapy for Acute and Subacute Ischemic Stroke in Taiwan. (18th April 2011) - Wei, Yi-Chia; Sun, Mao-Feng; Chang, Ku-Chou; Chang, Chee-Jen; Hung, Yu-Chiang; Lin, Yu-Jr; Chiu, Hsien-Hsueh Elley
Abstract : To reduce the health care burden of strokes, the Taiwan Department of Health launched the Pilot Scheme of the Health Policy in Stroke Adjuvant Acupuncture Therapy (HPSAAT) in 2006. This cross-sectional, hospital-based, match-controlled study at Chang Gung Memorial Hospital-Kaohsiung Medical Center during 2006∼2008 retrospectively evaluated the clinical characteristics of acute and subacute ischemic stroke patients who electively joined the HPSAAT. The study also evaluated the safety and clinical benefits of adjuvant acupuncture in treating acute and subacute ischemic stroke patients. Twenty-six HPSAAT participants and 52 age-sex matched random controls were enrolled. The stroke baseline of the HPSAAT participants was more severe than the non-HPSAAT controls. Although the stroke severity closely correlates to mortality and comorbidity, this study noted no significant complications in the HPSAAT participants during the acupuncture treatment course. Adjuvant acupuncture was considered safe at the acute and subacute stages of ischemic stroke. Due to uneven baseline severity, the clinical benefits in reducing neurological deficits and functional recovery were not concluded in this study.